KEJAHATAN SEKSUAL TERHADAP PEREMPUAN DAN ANAK PERSPEKTIF VIKTIMOLOGI - Sri Budi Raharjo; Ananda Megha Wiedhar Saputri; Windi Arini; Zahra Nabila Mua’lla; Salma Azizah (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2025)
Sexual violence against women and children is a serious violation of human rights that has a comprehensive impact—physical, mental, and social. In criminology, this crime is influenced by structural and cultural factors such as patriarchal domination, power imbalances, and a lack of legal protection and sexual education. The purpose of this study is to examine the characteristics of sexual crimes and assess the effectiveness of the legal system in protecting victims. The research was conducted using a normative-empirical legal method: the normative approach was conducted through an analysis of regulations such as the Child Protection Law and the TPKS Law; while the empirical approach involved interviews with law enforcement officials and victim advocates. The results indicate that although regulations are in place, their implementation is suboptimal, as evidenced by weak synergy between institutions, limited psychological support, and stigma that discourages victims from reporting. This study recommends a more holistic approach—including victim-centered legal reform, increased understanding of law enforcement, and public education. By combining criminological and legal analysis, it is hoped that the protection system for women and children can become more responsive and inclusive to the dynamics of sexual violence.